TEACHING PROFESSION-ORIENTED LEGAL ENGLISH TERMS TO FOREIGN LANGUAGE LEARNERS (Konferensiyalar | Conferences, 2024)
This research examines the efficiency of educating foreign language learners on profession-specific legal English vocabulary. It delves into creating new teaching methods customized to meet students' requirements in order to boost their grasp of legal English terminology. By blending theoretical concepts with practical techniques, the study aims to shed light on how foreign language learners can efficiently learn and remember specialized legal terms. The findings indicate that a focused strategy, integrating real-life situations and interactive learning approaches, significantly enhances students' understanding and utilization of profession- specific legal English vocabulary. This study adds to the current conversation on language education by presenting practical suggestions for educators looking to improve the learning of specialized legal vocabulary.